Analysis review on challenges and solutions to computer programming teaching and learning / Noor Hasnita Abdul Talib and Jasmin Ilyani Ahmad - Abdul Talib, Noor Hasnita; Ahmad, Jasmin Ilyani (2021)
Programming is creating or writing set of instructions that tells a computer to perform a task. Basically, programming is an important part in Computer Science as it is used to give instructions to the computer to understand and thus solve the problem. Hence, programming is a must-have skill for Computer Science students, especially dealing with technology that is evolving every day. However, there are challenges and difficulties facing by novice programmers in learning programming. This is due to the fact that most students find programming subjects difficult to learn and understand which results in not getting good grades in exams. Although various efforts have been taken to improve the learning and teaching process of programming subject, Computer Science teachers still face challenges to help students in mastering their programming skills. Therefore, this paper contributes to assisting novice programmers and teachers in enhancing their learning and teaching quality. Thus, this study aims to identify the factors contributing to the challenges and difficulties in teaching and learning programming and to review proposed solutions to overcome those challenges.